Modulation of Tryptophan/Serotonin Pathway by Probiotic Supplementation in Human Immunodeficiency Virus–Positive Patients: Preliminary Results of a New Study Approach - Giuseppe Corano Scheri (International Journal of Tryptophan Research, 2017)
Background: To date, no data are available regarding the effects of probiotics on the pathway of tryptophan/serotonin metabolism among human immunodeficiency virus (HIV) 1–infected individuals. Because a condition of dysbiosis might be responsible for the altered use of tryptophan described in this population, the aim of this study was to investigate the link between probiotic supplementation and serotonin levels in combined antiretroviral therapy–treated patients and the subsistence of an interplay with inflammation. Methods: We conducted a pilot study that included 8 HIV-positive subjects. We collected blood and fecal samples before and after 6 months of probiotic supplementation, to measure the level of serotonin in serum and tryptophan in stool, the expression of CD38 and HLA-DR on peripheral CD4+ T lymphocytes (as immune activation markers), the expression of indoleamine 2,3-dioxygenase 1 messenger RNA (mRNA) and IFN-γ mRNA (as markers of tryptophan metabolism and systemic inflammation). Results: After probiotic supplementation, we observed a significant increase in concentration of serum serotonin ( P  = .008) and a decreased level of tryptophan in plasma. Moreover, a significant reduction in CD38 and HLA-DR expression on the surface of peripheral CD4+ T cells ( P  = .008) and a reduced expression of indoleamine 2,3-dioxygenase 1 mRNA on peripheral blood mononuclear cells ( P  = .04) were observed. Conclusions: Considering that this probiotic (Vivomixx® in EU; Visbiome® in USA) has an influence on tryptophan metabolism, larger studies on this topic are needed.